1986
DOI: 10.1037/0022-0663.78.5.341
|View full text |Cite
|
Sign up to set email alerts
|

Media differences in children's story synopses: Radio and television contrasted.

Abstract: To evaluate the relative effectiveness of two media for conveying narrative information, young children and adults were presented the same story via either television or radio. Subjects then retold the story to an adult from memory. Media differences were found, with children in the radio condition showing significantly more errors in comprehension and memory than children in the television condition. Both the erroneous inclusion of inaccurate story content and the distortion of actual story characteristics oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…These multimedia learning principles can explain why young children's recall of the story line and story details improve when a narration is lavishly illustrated, as is typical of most paper and electronic storybooks for young children (Greenfield & Beagles-Roos, 1988;Hayes, Kelly, & Mandel, 1986). According to the dual-channel assumption, the advantage of books that include images in addition to text is that children thus have a chance to match verbal information with corresponding images because they are presented at the same time.…”
Section: The Potential Of Animation Background Sounds and Music In Smentioning
confidence: 92%
See 1 more Smart Citation
“…These multimedia learning principles can explain why young children's recall of the story line and story details improve when a narration is lavishly illustrated, as is typical of most paper and electronic storybooks for young children (Greenfield & Beagles-Roos, 1988;Hayes, Kelly, & Mandel, 1986). According to the dual-channel assumption, the advantage of books that include images in addition to text is that children thus have a chance to match verbal information with corresponding images because they are presented at the same time.…”
Section: The Potential Of Animation Background Sounds and Music In Smentioning
confidence: 92%
“…Even though detailed pictures make storybooks particularly suitable for extracting meaning and deriving unknown words from the book context (Carney & Levin, 2002;Greenfield & Beagles-Roos, 1988;Hayes et al, 1986), they may not always be needed or helpful because some readers are able to create mental images of story events from the words alone (Guttman et al, 1977). With age, easyto-follow texts that are highly concrete and engaging (e.g., interesting narrative passages) may readily elicit visual imagery (Carney & Levin, 2002).…”
Section: Differential Effects Of Additional Information Resourcesmentioning
confidence: 98%
“…Moreover, a text presentation allows a researcher to manipulate subtle aspects of a message and study the effects of messages independent of other variables (i.e./ nonverbal cues). However, a video portrayal results in a richer and more durable memory representation than monological or dialogical text alone (Hayes, Kelly & Mandel, 1986). In addition, scenes in a videotape can be dramatic and quite capable of arousing an emotional response by giving the observers more access to behavioral cues and allowing them to have more of a sense of participation in the encounter (Cappella & Street, 1989).…”
Section: Billigmentioning
confidence: 98%
“…But affect perception in middle childhood is poorly understood, leaving the developmental picture of these processes incomplete. Studies of exposure to media indicated that children tended to recall more visual than auditory information (Hayes & Kelly, 1984;Hayes, Kelly, & Mandel, 1986;Pezdek & Stevens, 1984). But these studies evaluated recall, rather than perceptual processing, of information.…”
Section: Multimodal Affect Perception and Developmentmentioning
confidence: 99%